Mycobacteria-specific prodrug to overcome phenotypic AMR in mycobacterium tuberculosis - Kumar, T. Anand; Birua, Shalini; Mallojjala, Sharath Chandra; Mukherjee, Piyali; Singh, Samsher; Kaul, Grace; Ramachandran, Aparna; Akhir, Abdul; Chopra, Sidharth; Gadgil, Chetan J.; Hirschi, Jennifer S.; Singh, Amit; et al. (Journal of Medicinal Chemistry, 2025)
Most front-line tuberculosis (TB) drugs are ineffective against hypoxic nonreplicating Mycobacterium tuberculosis (Mtb), largely due to poor permeability, leading to reduced drug accumulation and target engagement. To overcome this phenotypic antimicrobial resistance (AMR), we developed nitroheteroaryl prodrugs for Moxifloxacin (MXF), a front-line TB drug. These prodrugs are activated by bacterial nitroreductases (NTR), which are overexpressed in hypoxic Mtb. NTR-mediated electron transfer and protonation facilitate rapid cleavage of the protective group, releasing active MXF. The lead prodrug exhibited comparable efficacy to MXF in replicating Mtb and significantly enhanced lethality in nonreplicating Mtb. Drug accumulation studies confirmed a modest but significant increase in MXF levels in nonreplicating Mtb treated with the prodrug, suggesting improved permeability. A mathematical model integrating growth and drug-killing kinetics further elucidated how permeability differences impact lethality. Together, these findings highlight enzyme-activated prodrugs as a promising strategy to address phenotypic AMR in Mtb